The Influence Of Academic Innovation Capability, Organizational Innovation And Leadership Adaptability On Institutional Sustainability Performance Of Educational Institutions - Alief, Lazuardy; Subroto, Desty Endrawati; Mahardhani, Ardhana Januar; d'Ornay, Anastasia; Rahmad, Ilmi Noor; Safarudin, Muhamad Sigid (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The study that is now being conducted wants to measure how the ability to innovate academically, the organizational innovation, and the leadership that can adapt to change will affect the sustainability performance of educational institutions. Educators and administrative staff of higher education institutions made up the sample of 120 participants for the survey and the quantitative explanatory method was used to analyze the data. The analysis result showed that academic innovation capability, organizational innovation, and leadership adaptability were the independent variables, which had a significant positive effect on the sustainability performance of the institutions. As a result, the study not only augments the existing knowledge in educational management and institutional innovation literature but also gives practical tips to educational institutions on how to get better at sustainability by developing academic innovations, organizational innovations, and change-adaptive leadership.